Penyuluhan Pendidikan Kegamaan Melalui Kegiatan Keagamaan Jum’at Berkah (Wirid Yasin) Nurul Sa’adah - Leni Fitrianti (Yayasan Pelita Negri Belantaraya, Kab. Indragiri Hilir, Prov. Riau, 2024)
Religious education counseling through the women's wirid Yasin activity is a spiritual and social development strategy that aims to improve understanding and practice of religious values in daily life. This activity combines aspects of religious rituals in the form of reading Surah Yasin with educational sessions that discuss relevant religious topics. This approach provides a deep religious atmosphere while opening up space for dialog and reflection. Through the implementation of Wirid Yasin, participants, especially mothers, not only gain a better understanding of religion, but also strengthen their role as educators in the family. In addition, this activity serves as a medium to strengthen relationships between group members, create social solidarity, and build a community based on Islamic values. The method used in this community service activity is the lecture method with a PAR (Participatory Action Research) approach oriented towards community empowerment. The results of this activity show that wirid Yasin can be an effective tool in counseling religious education, as well as increasing religious awareness in the community. Keyword: Religious Education, Wirid Yasin, Spiritual Development, Mother's Role, Social Solidarity